Starch-based polymer composites for sustainable food packaging: Advances in bioplastic development - Raghunathan, Rakesh; Jeevarathinam, G.; Vadukkumchery Prasannan, Mayookha; Rustagi, Sarvesh; Asdaq, Syed Mohammed Basheeruddin (Wiley, 2025)
The growing environmental concerns associated with petrochemical‐based plastics, including their persistence, contribution to climate change, and adverse effects on ecosystems and human health, have accelerated the search for sustainable alternatives. Starch‐based bioplastics have emerged as a promising solution due to their biodegradability, renewability, and compatibility with existing food packaging technologies. This review comprehensively examines production mechanisms of starch‐based bioplastics, focusing on their formulation, structural modifications, and industrial applications. The role of plasticizers in improving flexibility and reducing brittleness is discussed. Their natural decomposition into environmentally benign byproducts supports a circular economy and aligns with global sustainability goals. However, the downside of using bioplastic is that the raw material used for its fabrication is also used for sustenance, and so a trade‐off between growing feedstock crops and food production is inevitable. The higher manufacturing costs of bioplastics as compared to conventional plastics are also a limiting factor. Hence, bioplastics do not completely serve as a long‐term panacea for problems associated with plastic pollution. This review therefore attempts to (i) enumerate the benefits of starch in food packaging, (ii) delineate the physical and chemical treatments that enhance hydrophobicity, mechanical strength, and thermal stability, (iii) suggest the proper disposal procedures to ward off health issues and to conserve the environment, and (iv) advocate the implementation of stringent recycling measures and emphasize on the policies and legislation for green transition. Future research should focus on optimizing polymer blends, reinforcing compatibility with synthetic and natural polymers, and advancing manufacturing techniques to enable widespread adoption in food packaging applications.